Psychological aspects of extremist activity - Sabirova, R.Sh.; Sairanuly, Ye. (Ye.A.Buketov Karaganda State University Publish hous, 2016)
This scientific article is devoted to the problem of the psychological aspects of such an important social problem as extremism.Extremism — is a complex phenomenon, despite the fact that its complexity is often difficult to see and understand. Today, all of us know about the nature and the reasons of extremism few. In this article the main theoretical approaches to definition of concept of extremism are considered. One of forms of manifestation of extremism is the terrorism. In article psychological aspects of terrorist activity, psychological factors the mechanisms inducing to membership in the extremist organization, specific features and psychological inclined to extremist activity are considered.
Экстремистік əрекеттің психологиялық аспектілері
Психологические аспекты экстремистской деятельности
Keywords: Extremism; extremist group; terrorism; religion; value; involvement; personality; behavior; attitude; individual; violence